Desain Dan Uji Coba Video Pembelajaran Animasi Menggunakan Canva Pada Materi Koloid - nurhusnasari, nurhusnasari; Lazulva, Lazulva (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
This research was instigated with the lack of student ability in processing the knowledge gained and the limited learning media in the learning process. This research aimed at finding out the validity and practicality levels of animation learning video on Colloid lesson. The development procedures were based on Borg and Gall model which was carried out in only 5 stages consisting of collecting data, planning, developing a product, field testing, and revising the initial product. The research was conducted at State Senior High School 10 Pekanbaru. Interview and questionnaire were used to collect data. The instruments of collecting data were validity and practicality test questionnaires. Animation video learning medium tested was valid with the percentages 88.57% (very valid) by media experts and 88.33% (very valid) by material experts, and it was tested practically with the percentages 95.38% (very practical) by 2 Chemistry subject teachers and 88.06% by 15 students (very practical). Based on these results, it was concluded that animation video medium on Colloid lesson was valid and practical so that product test could be carried out at the next stage.